Application of modified delphi in identifying the presence of Incomplete Contract (IC) in Private Finance Initiative (PFI) Projects - Mansor, Syaimasyaza; Abdul Rashid, Khairuddin; Ayob, Mohd Fairullazi; Hasan, Sharina Farihah (Construction Research Institute of Malaysia, 2017)
Incomplete contract (IC) is a contract that fails to state all the parties’ rights and obligations, has gaps and ambiguities in its terms and conditions. Past studies had reported that most contracts are incomplete to some degree, and this includes Private Finance Initiative (PFI) contracts. PFI involves the private sector to finance, design, construct, operate and maintain an asset through 20-30 years concession period. Due to its long duration, the contracting parties cannot specify all potential contingencies that might occur throughout the term of the contract and PFI contracts are inevitably incomplete. Sometimes IC is preferable because it provides the necessary flexibility to deal with uncertainty, but it also causes inefficiencies and costs, investment problem, contract amendment and so on. The objective of this paper is to report on a study to identify the presence of IC in PFI projects in Malaysia. The methodology used for the study is a two-round modified Delphi. This study is limited only to analyse PFI concession contracts in Malaysia. Based on extensive literature review and content analysis of eight PFI contracts, 12 clauses were identified as incomplete, and the findings become the basis of the semi-structured questionnaire for the modified Delphi. The aim of the modified Delphi is to achieve a consensus of experts’ opinion regarding the presence of IC in PFI projects. Results from the study show that the 12 identified clauses were deemed incomplete. Findings reported herein are considered significant towards effort in enhancing the effectiveness and efficiency of PFI contracts.